Supressão contralateral das emissões otoacústicas transientes em lactente com sífilis congênita - Nascimento, Leila Juliane Pinheiro do (2021)
Introduction: Syphilis is a global public health problem with complex challenges. In pregnant women, treponema paliidum can be transmitted to the fetus, leading to congenital syphilis, being a risk indicator for hearing loss, as there is evidence of the presence of sensorineural late hearing loss related to vertical transmission to the baby. Based on this premise, the efferent auditory pathway, in particular, the medial olivocochlear region and the outer hair cells, can be assessed by suppressing the otoacoustic supplied by transients, contributing to the identification of the maturation of important physiological processes of this pathway with congenital syphilis. Objective: Study 1 - To characterize the suppression of otoacoustic emissions by transients in children without risk indicators for hearing loss in the first year of life. Study 2 - Analyze the inhibitory effect of contralateral noise on otoacoustic emissions by transients in babies with congenital syphilis. Methodology: Study 1 - Systematic review registered in PROSPERO (nº CRD42020187035). The search took place in the EMBASE, LILACS, LIVIVO, PubMed, Scopus and Web of Science databases. The gray literature included Google Scholar, Open Gray and ProQuest, manual search of references of included studies and consultation with experts. Study 2 - Cross-sectional and prospective study approved by the Research Ethics Committee (nº 3,360,991). The total sample consisted of 35 babies divided into two groups (control -15 babies and study - 20 babies), all of which presented I-III-V waves in the BERA at 80 dB nNA and wave V at 30 dB nNA and the presence of non-linear TEOAE bilaterally. The suppression analysis was performed using linear TEOAE without noise and with white noise contralateral to 60 dB SPL. The mean of inhibition was obtained by subtracting the TEOAE without noise from the TEOAE with noise. Results: Study 1 - 3796 articles were found, after the selection steps 14 studies met the eligibility criteria. All studies showed efferent inhibition in neonates without risk indicators for hearing loss. Suppression was greater in studies that applied nonlinear and unfiltered click with averages greater than 1 dB in neonates in the first weeks of life. Study 2 - the response levels in the two test conditions were higher for females in the SG and males for the CG bilaterally. For both groups, TEOAE the response levels without noise were greater for the left ear, with the introduction of contralateral noise, the response levels were greater for the right ear. Both groups had a low occurrence of inhibition by ear, the SG presented inhibition in 5 (29.4%) subjects, the CG 3 (23.15%) bilaterally. However, the SG demonstrates a higher level of inhibition response for the left ear and the CG for the right. Conclusion: Study 1 - TEOAE suppression occurs in babies without risk indicators for hearing loss in protocols with different uptake characteristics, generating mean responses that do not allow a normative clinical value so far. Study 2 - The inhibitory effect of contralateral noise on TEOAE of babies with congenital syphilis does not differ from those without risk indicators for hearing loss.